C(sp3)−H bond activation by vinylidene gold(I) complexes: a concerted asynchronous or stepwise process? - Klein, Johannes E. M. N.; Nunes dos Santos Comprido, Laura; Hashmi, A. Stephen K. (Chemistry - a European journal, 2017)
A detailed analysis of the C(sp3)−H activation process by vinylidene AuI complexes is described based on an intrinsic bond orbital analysis. Based on our analysis this event can be divided into three phases: (i) hydride transfer, (ii) C−C bond formation, and (iii) σ to π rearrangement of the lone pair coordinated to Au. Small perturbations of the system lead to either a concerted asynchronous reaction, or a stepwise reaction featuring an intermediate with a C-H-C three-centre two-electron (3c-2e) bond. The role of π-donating substituents is highlighted and provides a way of controlling reactions of this type in future experimental studies.
Version of record online: October 19, 2017
Gesehen am 28.06.2018
Im Titel ist die Zahl 3 als Hochzahl dargestellt